Personalized and Biomarker-Guided Non-Invasive Brain Stimulation in Stroke Rehabilitation: A Systematic Review - Jauharotul Jannah; Firman Akbar Islami (Journal of Comprehensive Science, 2026)
Stroke causes significant disability, yet conventional rehabilitation demonstrates limited efficacy, particularly in severe cases. Non-invasive brain stimulation (NIBS) such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) offers a promising alternative; however, outcomes vary considerably due to the prevailing "one-size-fits-all" approach. This systematic review aims to evaluate the effectiveness of biomarker-guided, personalized NIBS in improving motor recovery following stroke. This systematic review was conducted in April 2026 in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search was performed across PubMed, the Cochrane Library, and Europe PMC. Inclusion criteria comprised randomized controlled trials (RCTs) involving adult stroke survivors receiving biomarker-guided or personalized NIBS including transcranial magnetic stimulation (TMS), rTMS, or tDCS compared to conventional rehabilitation or non-personalized NIBS protocols. Primary outcomes included motor recovery as measured by the Fugl-Meyer Assessment (FMA) and activities of daily living (ADL). Risk of bias was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool. Five RCTs encompassing 216 participants met the inclusion criteria, covering both the subacute and chronic phases of stroke recovery. Interventions included rTMS, theta-burst stimulation (TBS), and high-definition tDCS (HD-tDCS), guided by functional magnetic resonance imaging (fMRI), electroencephalography (EEG), and motor evoked potential (MEP) biomarkers. High-dose, fMRI-guided stimulation significantly improved FMA upper extremity scores compared to controls. HD-tDCS targeting individualized motor hotspots demonstrated sustained recovery at six-month follow-up. Intermittent TBS (iTBS) was more effective in patients with mild-to-moderate impairment than in those with severe deficits. Personalized NIBS guided by neuroimaging and neurophysiological biomarkers represents a significant advancement in stroke rehabilitation, yielding faster motor adaptation and superior functional outcomes compared to conventional approaches. Large-scale validation through adequately powered RCTs is warranted prior to routine clinical implementation.